Relationship of glycated hemoglobin, and fasting and postprandial hyperglycemia in type 2 diabetes mellitus patients in Malaysia - Lim, L.L.; Brnabic, A.J.M.; Chan, S.P.; Ibrahim, L.; Paramasivam, S.S.; Ratnasingam, J.; Vethakkan, S.R.; Tan, A.T.B. (Wiley Open Access, 2016)
Aims/Introduction: Studies on the relative contributions of fasting and postprandial hyperglycemia (FH and PPH) to glycated hemoglobin (HbA1c) in patients with type 2 diabetes have yielded inconsistent results. We aimed to assess the relationship by using continuous glucose monitoring in a multi-ethnic cohort. Materials and Methods: A total of 100 adults with type 2 diabetes were assessed with 6-day continuous glucose monitoring and HbA1c. Area under the curve (AUC) ≥5.6 mmol/L was defined as AUCTOTAL. AUC equal to or greater than each preprandial glucose for 4-h duration was defined as AUCPPH. The total PPH (AUCTPPH) was the sum of the various AUCPPH . The postprandial contribution to overall hyperglycemia was calculated as (AUCTPPH / AUCTOTAL) × 100%. Results: The present study comprised of Malay, Indian, and Chinese type 2 diabetes patients at 34, 34 and 28% respectively. Overall, the mean PPH significantly decreased as HbA1c advanced (mixed model repeated measures adjusted, beta-estimate = −3.0, P = 0.009). Age (P = 0.010) and hypoglycemia (P = 0.006) predicted the contribution difference. In oral antidiabetic drug-treated patients (n = 58), FH contribution increased from 54% (HbA1c 6–6.9%) to 67% (HbA1c ≥10%). FH predominance was significant in poorly-controlled groups (P = 0.028 at HbA1c 9–9.9%; P = 0.015 at HbA1c ≥10%). Among insulin users (n = 42), FH predominated when HbA1c was ≥10% before adjustment for hypoglycemia (P = 0.047), whereas PPH was numerically greater when HbA1c was <8%. Conclusions: FH and PPH contributions were equal in well-controlled Malaysian type 2 diabetes patients in real-world practice. FH predominated when HbA1c was ≥9 and ≥10% in oral antidiabetic drug- and insulin-treated patients, respectively. A unique observation was the greater PPH contribution when HbA1c was <8% despite the use of basal and mealtime insulin in this multi-ethnic cohort, which required further validation.